Surveillance Culture and Potential Resistance of Social Media in Egypt - Refaei, Dina (AUC Knowledge Fountain, 2022)
Social media companies have become dominant over their users. With digital capabilities that enable them to monitor, analyze and process users’ data, they are able to restrict users’ activities in accordance with their own policies. The present study examines the potential for users to encounter social media policies – specifically, privacy and content moderation policies imposed over activities on these platforms. The surveillance culture model is proposed to highlight surveillance perceptions among users and determine the factors that might affect users' intention to resist social media policies. A sample of 547 Egyptian social media users were surveyed. The findings showed that aware of relevant laws does not influence the user's perception of privacy on social media platforms. Instead, users assume that social media are monitoring their activities online for commercial purposes and to increase profits. While the majority were not subjected to the consequences of perceived policy violation, they are uncomfortable being surveilled. Further, perceptions of the reasons behind surveillance were found as a strong determinant of users’ concerns. Moreover, the findings highlight that an awareness or perception of surveillance does not relate to mitigating behaviors by users to resist or neutralize the effects of surveillance on them. Rather, social media surveillance is considered more as a pervasive phenomenon.